Analyse de la politique commerciale canadienne : rétrospective et synthèse - Séguin-Dulude, Louise (L'Actualité économique, 1979)
After a short review of the neo-classical theory of protection, the author presents the numerous models which were historically developed for the estimation of the national and regional impact of the Canadian tariffs. The author further compares a number of studies on the Canadian commercial policy, explains the divergences among them and, hopefully, identifies unsettled questions on the subject.